2021
DOI: 10.30699/mci.5.4.578-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Early Maladaptive Schemas on Coping Styles and Fear of Recurrence in Women With Breast Cancer: A Cross-Sectional Study

Abstract: Introduction:Maladaptive schemas influence the mental and physical health of patients. This study aimed to examine the role of early maladaptive schemas on coping styles and fear of recurrence in women with breast cancer (BC). Methods: This study was conducted; using a descriptive-correlational design. The research population included all female patients with BC who were referred to the radiotherapy ward of Five Hospitals in the center of Tehran from June to December 2020. The participants were 118 BC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Recently, many studies have explored the role of early maladaptive schemas on migraine, tension headaches, breast cancer, inflammatory bowel disease, etc. ( 19 21 ). According to the STM, basic emotional needs that are not appropriately satisfied during early life and repetitive adverse experience during childhood and adolescence form early maladaptive schema domains (EMSDs) in time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have explored the role of early maladaptive schemas on migraine, tension headaches, breast cancer, inflammatory bowel disease, etc. ( 19 21 ). According to the STM, basic emotional needs that are not appropriately satisfied during early life and repetitive adverse experience during childhood and adolescence form early maladaptive schema domains (EMSDs) in time.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of studies that dealt with the topic of the current research, the study [9] that was conducted in the Sata Marta region in Colombia, its results concluded that the most prominent scheme is the self-control scheme. As for the study [3], which was conducted on the role of early, maladaptive schemas in each of the coping methods and fear of relapse in women with breast cancer, where the results of the statistical analysis showed that both the schema of excessive impulse control and the schema of deficiency Incompleteness, the merging relationship, high demands, and incompetence were associated with fear of relapse, and the study confirmed the importance and role of early, maladaptive plans in coping with breast cancer. Another study [7] aimed to identify early maladaptive schemas in women with breast cancer.…”
Section: The Previous Studiesmentioning
confidence: 99%
“…However, although a direct relationship between early, maladaptive schemas and breast cancer has not been proven, there are studies that have shown that there is a between early, maladaptive schemas and other variables that predict the trajectory of the disease, such as [3], which found a relationship between maladaptive early schemas and fear of cancer relapse and quality of life according to [6] and [7] mixed symptoms of anxiety and depression according to [13].…”
Section: A Discussing the First Questionmentioning
confidence: 99%
See 2 more Smart Citations